Biobased Organic Nanoparticles: A Promising Versatile Green Tool for Novel Antimicrobial Agents for Improved Safety - Edith Dube; Grace Emily Okuthe (International Journal of Food Science)
Biobased organic nanoparticles possess nanoscale size, large surface area, tunable surface charge, and strong functionalization capacity, significantly enhancing their antimicrobial performance. Derived from renewable materials such as polysaccharides, proteins, and plant-based compounds, they provide a sustainable and ecofriendly alternative to synthetic antimicrobial agents. Their antimicrobial effects include disrupting microbial membranes, generating reactive oxygen species, and interfering with essential cellular processes, making them effective even against drug-resistant pathogens. Additionally, when used as drug delivery systems, they improve therapeutic outcomes by enhancing compound stability, bioavailability, and targeted delivery while minimizing toxicity. This review comprehensively analyses their structural features, mechanisms of action, and dual roles in infection control and drug delivery. It also addresses key challenges, including nanoparticle stability, scalability, and biosafety. The review concludes with future directions, emphasizing the need to optimize nanoparticle design, understand their interactions with microbial cells, and develop safe, cost-effective, and environmentally friendly synthesis methods to support their broader application in sustainable healthcare.